USING TMM (TALK A MILE A MINUTE) GAMES IN TEACHING STUDENTS’ SPEAKING SKILL TO THE TENTH GRADE STUDENTS OF SMK PSM 2 KAWEDANAN MAGETAN IN THE SCHOOLING YEAR 2013/2014 - Dea Ayu Nirmala (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
The purposes of the research are to describe the procedure of the uses of TMM game, to identify the advantages of using TMM game, and to know disadvantages of using TMM (Talk a Mile a Minute) game in teaching students’ speaking skill. The result of the research shows that the applications of TMM (Talk a Mile a Minute) game can make students easier in understanding the lesson in speaking skill. The procedure of talk a mile a minute game in activity of teaching speaking by using talk a mile a minute game for the tenth grades at SMK PSM 2 Kawedanan, Magetan at in schooling year of 2013/2014 is appropriate with the lesson plan and syllabus which teacher makes before. After using TMM game, there are some the advantages and the disadvantages of this game. The advantages are, to help students in teaching speaking skill, to increase the student’s motivation, as an innovation in teaching process, and this game can make students enthusiastic in teaching learning process. The disadvantages of this game are that the students only make a joke with their friends, make class noisy